A SYSTEMATIC LITERATURE REVIEW TO A CONCEPTUAL FRAMEWORK FOR GREEN SUPPLY CHAIN MANAGEMENT EVALUTION OF PLTU - Aprilisia T, Nita; Sumantri, Yeni; Himawan, Rakhmat (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2025)
Green Supply Chain Management (GSCM) is a strategic approach that integrates sustainability principles in the supply chain to minimize negative impacts on the environment. GSCM performance measurement still faces challenges, especially in determining the most relevant indicators. This study aims to analyze various GSCM performance indicators based on a review of 20 previous studies. The method used is a systematic literature study, by reviewing objects, analysis methods, and results obtained from various studies. The results show that Environmental Performance, Supply Chain Sustainability, and Operational Performance are the main focus in the implementation of GSCM. In addition, Economic/Financial Performance, Logistics Performance, and Regulatory Compliance also play an important role in improving efficiency and industry compliance with regulations. Various analytical methods such as Fuzzy-DEMATEL, Analytic Network Process (ANP), and Data Envelopment Analysis (DEA) were used in previous studies. Therefore, a holistic, system-based approach is needed to optimize GSCM implementation in various industrial sectors.